Pendekatan Contextual Teaching and Learning pada pembelajaran Peredaran Darah Manusia bagi siswa kelas V SD Negeri 2 Pagutan Kecamatan Manyaran, Kabupaten Wonogiri Tahun Pelajaran 2019/2020 - Pratiwi Suci Widodo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In the process of student learning activities, it is less than optimal because during the learning process students tend to be passive and the teacher is dominant in applying conventional learning. This research was conducted with a Classroom Action Research (CAR) design in two cycles. The results showed that the application of the Contextual Teaching Learning approach could increase interest and learning outcomes. Student learning outcomes in the initial conditions on average were 57 with the number of students who completed 26%. Cycle I learning outcomes increased to an average of 70 with the number of students who completed as many as 65% of students. In cycle II, learning outcomes increased again to an average of 82 with 100% of students who completed. Based on the analysis, it can be concluded that the application of Contextual Teaching Learning approach can increase interest and learning outcomes of human blood circulation in fifth grade students of SD Negeri 2 Pagutan I Semester I Academic Year 2019/2020.